Identification and Validation of lncRNA-AC087588.2 in Lung Adenocarcinoma: A Novel Prognostic and Diagnostic Indicator - Jiang, Xiulin; Chen, Xi; Guo, Jishu; Zhou, Fan; Pu, Jun; Mutti, Luciano; Niu, Xiaoqun (Frontiers in Molecular Biosciences, 2022)
Lung adenocarcinoma (LUAD) is the most common histological lung cancer, and it is the leading cause of cancer-related deaths worldwide. Long noncoding RNAs (lncRNAs) have been implicated in the initiation and progression of various cancer. LncRNA-AC087588.2 (ENSG00000274976) is a novel lncRNA that is abnormally expressed in diverse cancer types including LUAD. However, the clinical significance, prognostic value, diagnostic value, immune role, and the potential biological function of AC087588.2 LUAD remains elusive. In this study, we found that AC087588.2 was up-regulated and associated with a poor prognosis in LUAD. In addition, univariate and multivariate Cox regression analysis indicated that AC087588.2 could be an independent prognostic factor for LUAD. Functionally, knockdown of AC087588.2 restrained LUAD cell proliferation and migration in vitro. This finding provided a comprehensive view of the AC087588.2 in LUAD, thereby highlighting its potential role in diagnosis and prognosis of LUAD.